Interpreting insect behavior through the lens of executive functions - Baran, Bartosz; Obidziński, Michał; Hohol, Mateusz (Frontiers in Behavioral Neuroscience, 2025)
Despite miniature brains, insects exhibit flexible, adaptive, and goal-directed responses. Behaviors indicating rule abstraction and complex decision-making challenge the long-standing view of insects as rigid organisms limited to fixed reflexes. Here, we propose a new perspective: interpreting insect behavior through the lens of executive functions (EF). EF refers to a set of cognitive processes enabling behavioral control in situations requiring goal-directed action or adaptation to demanding conditions. Central among EF are inhibition (suppressing automatic, task-irrelevant responses), shifting (switching between strategies or rules), and updating (maintaining and revising relevant information), yet working memory, attention, planning, decision-making, and metacognition are also related to a widely understood set of EF. We argue that insect cognition can be productively reconsidered using the EF framework. Many behaviors documented in the literature align with EF components, even if not explicitly labeled as such. Others can be reinterpreted as EF-driven. Importantly, we show that EF-based interpretations support testable predictions: if executive control is involved, behavior should follow developmental trajectories, exhibit trade-offs between speed and accuracy, and adapt to changing contexts–patterns not expected from fixed heuristics or reflexes. Nonetheless, applying EF concepts to insects comes with challenges. Standard EF paradigms were originally developed to test human participants and often rely on language and explicit task instructions. Moreover, superficially flexible behaviors may still result from specialized, domain-specific routines rather than general cognitive control. Nevertheless, when used carefully, the EF perspective provides a structured, functional framework for studying insect cognition, enabling precise comparison across species with well-established concepts.